Dual‐wideband differential bandpass filter with intrinsic common‐mode suppression based on hybrid transmission structure. Issue 10 (3rd August 2020) - Liang, Zhelong; Wang, Litian; He, Ming; Li, Xiaqing; Li, Zhao; Ji, Lu; Zhang, Xu; Chen, Haihua; Wang, Hongpeng; Cao, Xuewei
Abstract: Based on the microstrip‐line/slot‐line hybrid transmission structure, a novel method of realizing dual‐wideband differential bandpass filter (DDBPF) is proposed and demonstrated in this paper. By virtue of hybrid transmission structure, the proposed DDBPF has intrinsic common mode (CM) rejection. Moreover, the dual‐wideband transmission performance of differential mode (DM) signal can be approached by using two dual‐mode stub‐loaded stepped‐impedance resonators. The two passbands of the proposed DDBPF are respectively centered at 2.76 GHz and 4.12 GHz which fractional bandwidths are 20.7% and 11.4%. The DM harmonic suppression can extend to 43.5 GHz with rejection level of 13 dB. The CM attenuation of DDBPF can reach 60 dB within DM passband. Furthermore, the CM suppression with attenuation level of 20 dB is ranging from 0.5 GHz to 43.5 GHz. The measurement results are in good agreement with the simulation results, which validates the effectiveness of proposed design methodology.